A Multi Objective Optimization Model for Redundancy Allocation Problems in Series-Parallel Systems with Repairable Components - Maghsoud Amiri; Mohammadreza Sadeghi; Ali Khatami Firoozabadi; Fattah Mikaeili (International Journal of Industrial Engineering and Production Research, 2014)
The main goal in this paper is to propose an optimization model for determining the structure of a series-parallel system. Regarding the previous studies in series-parallel systems, the main contribution of this study is to expand the redundancy allocation parallel to systems that have repairable components. The considered optimization model has two objectives: maximizing the system mean time to first failure and minimizing the total cost of the system. The main constraints of the model are: maximum number of the components in the system, maximum and minimum number of components in each subsystem and total weight of the system. After establishing the optimization model, a multi objective approach of Imperialist Competitive Algorithm is proposed to solve the model.